Ternary blends of Portland cement, bottom ash and silica fume: Compressive strength of mortars and phase characterizations - Arnon Chaipanich (2018)
Bottom ash, a by-product from coal power plant was blended with Portland cement and silica fume to produce ternary blend mixes. Compressive strength of mortars and phase characterizations were investigated. Bottom ash was used to replace part of Portland cement at 10%, 20% and 30% by weight and silica fume was used as an additional material at 5% by weight. Compressive strength test results of blend cement mortars show an increase in compressive strength when silica fume was used in the mix in addition to that of bottom ash. The benefit of silica fume addition was clearly seen especially for mixes with higher bottom ash content (30% bottom ash), compressive strength was significantly enhanced to exhibit strength similar to that of Portland cement control. Thermogravimetric analysis confirms the pozzolanic reaction of silica fume showing an increase in calcium silicate hydrate (C-S-H) and gehlenite hydrate (C 2 ASH 8 ) phases when silica fume was added. X-ray diffraction traces, in general, showed a reduction in Ca(OH) 2 peaks while Scanning Electron Microscopy showed a denser cement matrix when silica fume was added.